Animation-based Learning Effectiveness in Physics Learning. Issue 1 (February 2021) - Rahman Aththibby, Arif; Mundilarto,; Widodo,
Abstract: 21 st century education requires teachers who can adapt to technological developments, including for physics teachers. Physics as one of the branches of science, studying and analyzing quantitatively the symptoms or natural processes. Physics is a science that studies the parts of nature and the interactions within them. The problem that is always experienced by students is the low learning outcomes caused by the lack of motivation in learning physics. Computer animation can be a solution offered to present effective learning in physics learning. Based on the results of the study it is known that the use of computer animation has a significant effect on the learning outcomes of physics and also the motivation of students in learning physics.